Numerical study of a horizontal shower water heat recovery system - Purghel Dragoș; Teodosiu Cătălin Ioan (E3S Web of Conferences)
The objective of this work is to numerically study the performance of a drain water heat recovery (DWHR) device prototype intended for small shower trays. The numerical model is based on Computational Fluid Dynamics (CFD) approach. The simulations were performed for unbalanced and balanced configurations in terms of waste water flow rate and cold water flow rate. The results achieved show that the thermal effectiveness of the proposed DWHR system is between 15-27% and the Number of Transfer Units (NTU) is among 17-37%, with higher values for the unbalanced configuration. Based on these values, it can be concluded that the designed DWHR unit leads to satisfactory results considering cost-effectiveness reasons and maintenance.